TRANSFORMASI KEUANGAN DIGITAL SISTEM PEMBAYARAN NON TUNAI DI DESA WISATA SELASARI KEACAMATAN PARIGI KABUPATEN PANGANDARAN - Ramdani, Eggy Armand; Andini, Ria; Sari, Rika (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2024)
This research aims to explain the transformation process carried out by the Selasari Tourism Village, which continues to develop and has been awarded an Advanced Category Tourism Village by the Ministry of Tourism and Creative Economy of Republic Indonesia. The development of the Selasari Tourism Village in carrying out this transformation is an illustration of how an ordinary village becomes a national class tourist village and gradually carries out its digital financial transformation independents. The research method used is descriptive qualitative research through field and library methods. The research results show that the payment system used in the Selasari Tourism Village is cash and non-cash payments. The digital financial transformation of the payment system in the Selasari Tourism Village has been ongoing since 2017, starting from transfers between management accounts only. In 2019, accounts began to be created in the name of BUMDes Selasari. So far, Selasari Tourism Village has 3 general accounts. Other payment systems adapt to the requests from visitors, E-money and QRIS. Efforts made by the Selasari Tourism Village to overcome problems in the digital financial transformation process in the payment system are by advocating for the provision of cellular operator transmission towers, providing direct socialization and training to the community and using non-cash payments that are already available.